2005
DOI: 10.1111/j.1945-5100.2005.tb00366.x
|View full text |Cite
|
Sign up to set email alerts
|

The onset of metamorphism in ordinary and carbonaceous chondrites

Abstract: Received May 18, 2004; revision accepted November 3, 2004) Abstract-Ordinary and carbonaceous chondrites of the lowest petrologic types were surveyed by Xray mapping techniques. A variety of metamorphic effects were noted and subjected to detailed analysis using electron microprobe, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and cathodoluminescence (CL) methods. The matrix in the least metamorphosed chondrites is rich in S and Na. The S is lost from the matrix at the earlies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
456
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 343 publications
(499 citation statements)
references
References 66 publications
(132 reference statements)
38
456
5
Order By: Relevance
“…Specifically, Palme et al (1988) and Palme and Boynton (1993) identified a number of reasons why the two-component model failed to explain the observed trend, including the fact that chondrules contain a significant amount of volatiles and therefore are not "volatile-depleted" as required by the Anders model (although parent body effects may have played a role [e.g., Grossman and Brearley 2005]). Palme (2001) also argued that the Rb/Sr inventory of chondritic meteorites is inconsistent with the molecular cloud inheritance theory, though Yin (2005) outlines counter arguments.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Palme et al (1988) and Palme and Boynton (1993) identified a number of reasons why the two-component model failed to explain the observed trend, including the fact that chondrules contain a significant amount of volatiles and therefore are not "volatile-depleted" as required by the Anders model (although parent body effects may have played a role [e.g., Grossman and Brearley 2005]). Palme (2001) also argued that the Rb/Sr inventory of chondritic meteorites is inconsistent with the molecular cloud inheritance theory, though Yin (2005) outlines counter arguments.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Cr concentrations in olivine are quite variable. Grossman and Brearley (2005) made a detailed study of Cr in olivine in ordinary and CO chondrites and concluded that Cr diffused out of olivine at very low temperatures. Since the Cr diffusion rate in olivine is not fast compared with those of other cations (Ito and Ganguly, 2006), the Cr loss was probably promoted by the presence of water.…”
Section: Discussionmentioning
confidence: 99%
“…Petrologic type 3 chondrites could be subdivided into types 3.0 to 3.9 based on their characteristics of thermoluminescence and compositions of minerals (Sears et al 1980;Scott & Jones 1990;Scott et al 1994;Grossman & Brearley 2005;Bonal et al 2006). It is suggested that type 3.0 and 3.1 chondrites experienced lower peak temperatures of ∼ 200 -400…”
Section: Isotopic Diffusion In Thermally Evolving Planetesimalsmentioning
confidence: 99%